A sexually dimorphic pre-stressed translational signature in CA3 pyramidal neurons of BDNF Val66Met mice. Issue 1 (December 2017) - Marrocco, Jordan; Petty, Gordon; Ríos, Mariel; Gray, Jason; Kogan, Joshua; Waters, Elizabeth; Schmidt, Eric; Lee, Francis; McEwen, Bruce
Abstract Males and females use distinct brain circuits to cope with similar challenges. Using RNA sequencing of ribosome-bound mRNA from hippocampal CA3 neurons, we found remarkable sex differences and discovered that female mice displayed greater gene expression activation after acute stress than males. Stress-sensitive BDNF Val66Met mice of both sexes show a pre-stressed translational phenotype in which the same genes that are activated without applied stress are also induced in wild-type mice by an acute stressor. Behaviourally, only heterozygous BDNF Val66Met females exhibit spatial memory impairment, regardless of acute stress. Interestingly, this effect is not observed in ovariectomized heterozygous BDNF Val66Met females, suggesting that circulating ovarian hormones induce cognitive impairment in Met carriers. Cognitive deficits are not observed in males of either genotype. Thus, in a brain region not normally associated with sex differences, this work sheds light on ways that genes, environment and sex interact to affect the transcriptome's response to a stressor. Animals' response to acute stress is known to be influenced by sex and genetics. Here the authors performed RNA-seq on actively translated mRNAs in hippocampal CA3 neurons in mice, and document the effects of sex and genotype (i.e., BDNF Val66Met) on acute stress-induced gene expression.